The Effect Of Liquidity, Solvency And Profitability On Stock Prices (Study of Classification J Infrastructure Companies Listed on the Indonesian Stock Exchange for the 2020-2023 Period) - Rendiyansyah, Rois; Kresnandra, Anak Agung Ngurah Agung (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This research investigates the empirical relationship between liquidity, solvency, and profitability and stock prices of infrastructure companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2023 period. Employing a sample of 22 infrastructure companies selected through purposive sampling, the study utilizes multiple linear regression analysis with current ratio, debt-to-equity ratio, and return on assets as independent variables. The findings indicate that liquidity exerts a negative influence on stock prices, while profitability demonstrates a positive correlation. Notably, solvency does not exhibit a significant impact on stock prices. These results suggest that investors in infrastructure companies may prioritize high profitability over high liquidity when making investment decisions. The study contributes to the existing literature by providing empirical evidence on the financial determinants of stock prices in the infrastructure sector and offers insights for future research.